Family’s Role in Helping Drug Abuser Recovery Process - Devy Mulia Sari; Mohammad Zainal Fatah; Ira Nurmala (Universitas Airlangga, 2021)
Background: The National Narcotics Board or Badan Narkotika Nasional (BNN) survey results found the prevalence of drug abuse in 2015 amount 42,900 people, and an increase of 20.84% in 2016, which amounted to 51,840 people. As a result of drug abuse, drug abusers often experience health problems both physically and mentally due to the influence of drugs or the environment that makes drug abusers depressed. One of the health treatments for drug abusers that can be done to motivate drug abusers is to provide family support. The family is a source of social support because, in family relationships, mutual trust is created. Objective: This research was conducted to determine how the family’s role based on Kroenke helped to recover the health of drug abusers from deciding to stop drug abuse. The government can later consider this research’s benefits in creating a family-based drug abuse prevention and recovery program. Methods: This study uses a review of international articles. The articles used are twenty articles published in the last ten years. Result: Research shows that the family’s role in helping recovering drug users’ health drug users’ health is different but still has the same goal. Support provided is based on the cause of individuals to commit drug abuse. Support could be provided in the form of assessment support, instrumental, informational, and social. A good family role’s functioning makes the recovery process more effective because an addict will feel motivated by their support. Conclusion: The research conducted that the family’s role is essential for the recovery of the health of drug addicts, providing a stimulus for change to stop drug abuse. The family’s ability and function in explaining the addict’s self-control varies according to how the response and the intensity of family support provided to the addict.